Music teachers and their pupils: musical activities, self-perceptions, and attitudes to music - Milhano, Sandrina (2021)
This paper examines the influences of music teachers’ on primary school pupils’ musical activities, self-perceptions, and attitudes to music. We will discuss issues that involve results about the relations between music teachers’ and their profile according to their musical background, academic training, and professional and artistic activities’, with their pupils musical activities, self-perceptions, and attitudes to music. The main findings were gathered from two studies that were carried out in two phases (year 1 and 2): the Pupil Questionnaire Study and the Music Teachers Study. The total participants were 9 music teachers carrying out extracurricular musical activities in 16 Portuguese primary schools and 406 children from grades 3 and 4 (aged 8-11 years). The findings were drawn from the connections and relationships found between the results from the Music Teachers Study and the results obtained through the Pupil Questionnaire Study, in each school. These last results involve the description of pupils’ perceived activities during extracurricular music classes, musical attitudes, and self-perceptions to music, and their perceptions of their music teachers in school during their participation in the musical activities. The main findings are discussed according to five main themes: a) Musical activities: singing and playing musical instruments and music notation learning. b) Pupils’ self-assessments of themselves on the activities of singing, playing musical instruments and notation learning. c) Pupils' self- perceptions of themselves in two aspects: musicality and competence in music classes. d) Pupils’ attitudes to music; and e) Pupils’ attitudes and perceptions of their music teacher. Findings across the sample suggested that music teachers background, academic, professional and artistic, did not seem to have influenced the musical activities they have provided to their pupils’ in the musical activities, except in some cases for the use of the recorder in classes. The same teachers in different schools developed different musical activities. Music teachers do not seem to significantly influence pupils’ musical skills assessments; however, the ‘time effect’ was an interesting find. That is, the time pupils’ spent participating in the extracurricular musical activities may have influenced more pupils’ selfassessments more than the music teachers possibly did. Results also suggested that pupils’ attitudes and self-perceptions of music do not appear to be influenced by particular aspect of a teacher’s profile, background or experience, and more specifically, the presence of pedagogical training appears to have little or no impact. Also, it was not possible to establish a direct connection between the ways pupils’ perceived themselves as being ‘musical’ or not, with their attitudes to music. No associations were found between music teachers’ academic backgrounds and general ‘profile’ and the aspects relating to how much pupils’ felt they were learning in the music classes and towards their idea of having a profession connected to music. In, summary, is was not really possible to establish with any degree of consistency that a connection exists across the sample between pupils’ musical activities, self-perceptions, and attitudes to music and their music teachers’ academic background during both phases. We will also discuss some implications of this study for music teachers training.